The complete mitochondrial genome of the Pale-legged Leaf-Warbler Phylloscopus tenellipes (Aves: Phylloscopidae) from Maor Mountain, China. Issue 7 (3rd July 2022) - Yu, Wei; Cui, Shuang; Chen, Junda; Meng, Dehuai; Zhou, Xiaoyu; Teng, Liwei; Liu, Zhensheng
Abstract: The Pale-legged Leaf-Warbler ( Phylloscopus tenellipes ) (Swinhoe, 1860) is an olive-brown warbler that is extensively dispersed in Asia. We sequenced the whole mitochondrial genome of a Pale-legged Leaf-Warbler collected on Maor Mountain, Heilongjiang Province, China. The mitochondrial genome is 16, 972 bp and contains 13 protein-coding genes, two rRNA genes, 22 tRNA genes, and one control region (CR). The CR is 1098 bp. The nucleotide sequence is composed of 29.11% A, 22.98% T, 14.64% G, and 33.27% C. Phylogenetic research revealed that P. tenellipes is closely related to Phylloscopus borealoides .